Age-dependent alterations of decorin glycosaminoglycans in human skin - Li, Yong; Liu, Ying; Xia, Wei; Lei, Dan; Voorhees, John J.; Fisher, Gary J. (Scientific reports, 2013)
Proteoglycans, a family of glycosaminoglycan (GAG) conjugated proteins, are important constituents of human skin connective tissue (dermis) and are essential for maintaining mechanical strength of the skin. Age-related alterations of dermal proteoglycans have not been fully elucidated. We quantified transcripts of 20 known interstitial proteoglycans in human skin and found that decorin was the most highly expressed. Decorin was predominantly produced by dermal fibroblasts. Decorin was localized in dermal extracellular matrix with GAG bound to type I collagen fibrils. Analysis of decorin extracted from young (21–30 years) and aged (>80 years) sun-protected human buttock skin revealed that decorin molecular size in aged skin is significantly smaller than in young skin. The average size of decorin protein did not alter, indicating size of GAG chain is reduced in aged, compared to young skin. This age-dependent alteration of decorin GAG may contribute to skin fragility of elderly people.